2022
DOI: 10.3390/horticulturae8020107
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Thermal Dissipation Probes for Date Palm (Phoenix dactylifera L.)

Abstract: The quantification of water flow through the stem is vital for date palm (Phoenix dactylifera L.) to promote a good water stress management. The thermal dissipation probe (TDP) method developed by Granier is widely used to evaluate transpiration of forest trees; however, there are contradictory reports regarding its reliability. Considerable errors in estimated sap flux density, which might be due to a lack ofspecies-specific calibrations. The TDP method uses a mathematical model that is based on an empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This may be due to the small specificity of coefficient β. There also showed an extensive range of variation in coefficient α and a slight variation in coefficient β [7,21,22,24]. Furthermore, it has been observed that the CV exhibits a significantly negative correlation with coefficient α, whereas its correlation with β remains insignificant.…”
Section: Differences Before and After Calibration Of The Sap Flow For...mentioning
confidence: 92%
See 2 more Smart Citations
“…This may be due to the small specificity of coefficient β. There also showed an extensive range of variation in coefficient α and a slight variation in coefficient β [7,21,22,24]. Furthermore, it has been observed that the CV exhibits a significantly negative correlation with coefficient α, whereas its correlation with β remains insignificant.…”
Section: Differences Before and After Calibration Of The Sap Flow For...mentioning
confidence: 92%
“…To test the relationship between wood structures and the calibration parameters of the Granier formula on a broader scale, both measured data in this study and published data were used. The published calibration and wood structure data were directly retrieved from tables or the TRY database [2,6,8,10,11,15,16,[18][19][20][21][22][23][24]26,27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. To enlarge the data range, the published calibrated species that found only one or two structure parameters were also included in this analysis.…”
Section: Data Extraction and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental conditions can have a significant impact on the pollination and fertilization processes. Optimal temperature is essential for different stages of sexual reproduction in flowering plants, such as pollen formation, pollen transfer, the readiness of stigmas for pollen, pollen germination, the growth of pollen tubes, double fertilization, and seed development (Hedhly et al, 2003(Hedhly et al, , 2005Snider and Oosterhuis, 2011;Zulkarnain et al, 2019;Ali-Dinar et al, 2021;Alla et al, 2022). Any form of stress during these stages can result in sterility and, ultimately, reduce crop yields.…”
Section: Introductionmentioning
confidence: 99%